Religious Gaslighting dalam Komunitas Muslim: Kritik Pendidikan Islam Terhadap Manipulasi Psikologis Manipulasi Psikologis Atas Nama Agama - Reina Aulia Revi; Misra Misra (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Religious gaslighting is a form of psychological manipulation that uses religious authority and teachings to question or doubt a person's perceptions, emotions, and experiences, so that the victim feels guilty or unfaithful. In the context of the Muslim community, this practice can occur when religious understanding is used narrowly and authoritarianly, suppressing freedom of thought, and perpetuating power imbalances—both in family relationships, communities, and religious institutions. This article examines the phenomenon of religious gaslighting from the perspective of critical Islamic education, with the aim of dismantling manipulative patterns wrapped in religious narratives. The approach used is qualitative-descriptive with literature analysis of classical and contemporary Islamic sources, as well as interdisciplinary studies in the fields of religious psychology and educational philosophy. The results of the study show that religious gaslighting is not only a matter of individual morals, but also part of an authoritarian social and cultural structure that needs to be countered through liberating (ta'dib) and transformative Islamic education. Islamic education based on the values ​​of justice (al-‘adl), compassion (rahmah), and deliberation can be a critical tool for building a healthy spiritual awareness and freeing people from the shackles of manipulative authority. Thus, education has a central role in forming a generation of Muslims who are able to distinguish between the authenticity of Islamic teachings and their misuse in the practice of power.